The touch of the present : educational encounters, aesthetics, and the politics of the senses - Todd, Sharon, 1962- (SUNY series, transforming subjects: psychoanalysis, culture, and studies in education., 2023)
Explores the importance of the body and the senses in educational encounters, drawing out the aesthetic and political dimensions of educational practices.